Tracing Frameworks of Visibility in Open Kitchen Environments - (:unkn) unknown (My University, 2025)
Open kitchens “represent a multifaceted metaphor for the way diners regard the experience of eating out and the way many chefs regard their role” (Bruni 2005). New York Times Opinion writer Frank Bruni suggests complex interpretations of the open kitchen environment organized by different social actors. Existing literature on open kitchens conceptualizes visibility in three distinct ways: 1) as a mechanism of social control (i.e., surveillance); 2) as a mechanism of communication; and 3) as a mechanism of authentication. However, little is known about how actors in the open kitchen environment interpret and navigate visibility in practice. Drawing on 10 hours of participant observations and 12 semi-structured interviews in Milwaukee’s restaurant industry, this study traces how visibility is structured, interpreted, and negotiated by various restaurant actors. Findings indicate that prior conceptualizations of visibility in open kitchens interact in ways patterned by material, sensory, and epistemological boundaries indicating field position. By tracing visibility across multiple sub-disciplinary boundaries, this study contributes to ongoing efforts to bridge currently isolated sociological theoretical frameworks.
Keywords: Social research